1997
DOI: 10.1002/(sici)1098-2302(199709)31:2<149::aid-dev8>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior of maternally separated gibbons (Hylobates)

Abstract: The effect of early maternal separation on the sexual behavior of captive gibbons was investigated because (a) maternal separation compromises sexual behavior of some nonhuman primates and (b) adequate sexual behavior is essential to species propagation. Most of the maternally separated gibbons (24/31) were sexually proficient. Sexual behavior overall did not differ significantly in relation to species, sex, origin (wild‐ vs. captive‐born), or type of rearing facility (home vs. zoo). Sexual proficiency was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The unnaturally reared gibbons in the present study exhibited not only significantly higher fecal GC levels than parent-reared animals, but also appeared to show more abnormal, nonsocial behavior. In contrast to the influence of rearing experience on physiology, i.e., adrenocortical activity, later in life, the influence of rearing on adult behavior is very well documented (Goin and Gust 1998;Meder 1988;Mootnick and Nadler 1997). Behavioral abnormalities toward conspecifics or humans in unnaturally reared primates are often related to a lack of adequate social learning and imprinting on humans in early infancy (Porton and Niebruegge 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The unnaturally reared gibbons in the present study exhibited not only significantly higher fecal GC levels than parent-reared animals, but also appeared to show more abnormal, nonsocial behavior. In contrast to the influence of rearing experience on physiology, i.e., adrenocortical activity, later in life, the influence of rearing on adult behavior is very well documented (Goin and Gust 1998;Meder 1988;Mootnick and Nadler 1997). Behavioral abnormalities toward conspecifics or humans in unnaturally reared primates are often related to a lack of adequate social learning and imprinting on humans in early infancy (Porton and Niebruegge 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Because gibbons are canopy specialists in tall forests, behavioral studies present great difficulties, and information on their social and especially reproductive behaviors in the wild is very limited (Palombit 1994a). Researchers have gathered most sexual observations on gibbons from captives (Mootnick and Baker 1994;Mootnick and Nadler 1997;Pan 2000;Yang 1998) except those from white-handed gibbons (Hylobates lar), siamang (Symphalangus syndactylus), and hoolock gibbons (Hoolock hoolock) (Ahsan 2000;Alfred and Sati 1987;Carpenter 1940;Chivers 1978;Dewsbury and Pierce 1989;Edwards and Todd 1991;Ellefson 1974;Koyama 1971;). Hence captivity-induced abnormalities and small sample sizes may affect our current understanding of gibbon reproductive behaviors.…”
Section: Introductionmentioning
confidence: 94%
“…In captive primates, it usually occurs in situations that are stressful to the individual. For example, Bernstein et al (1963) reported self-biting in wild-born but laboratory-housed gibbons in response to novel objects; Mootnick and Nadler (1997), in a survey of sexual behavior in gibbons in a variety of captive settings, found selfbiting in several individuals in response to stress, and Mitchell et al (1988) found self-directed aggression in golden-bellied mangabeys (Cercocebus galeritus chrysogaster) to occur particularly in captive-born females, especially in stressful situations. Investigating the correlates of SIB is rarely by itself the object of the studies, though Skyner et al (2004) noted that the SIB of a captive pileated gibbon (Hylobates pileatus) increased when it was exposed to large human audiences.…”
mentioning
confidence: 99%